Epitope-mapping of the glycoprotein from Crimean-Congo hemorrhagic fever virus using a microarray approach - Fritzen, Amanda; Risinger, Christian; Korukluoglu, Gulay; Christova, Iva; Corli Hitzeroth, Arina; Viljoen, Natalie; Burt, Felicity Jane; Mirazimi, Ali; Blixt, Ola (PLoS neglected tropical diseases, 2018)
Crimean-Congo hemorrhagic fever virus (CCHFV) causes severe acute human disease with lethal outcome. The knowledge about the immune response for this human health threat is highly limited. In this study, we have screened the glycoprotein of CCHFV for novel linear B-cell epitopic regions using a microarray approach. The peptide library consisted of 168 synthesized 20mer peptides with 10 amino acid overlap covering the entire glycoprotein. Using both pooled and individual human sera from survivors of CCHF disease in Turkey five peptide epitopes situated in the mucin-like region and GP 38 (G15-515) and GN G516-1037 region of the glycoprotein were identified as epitopes for a CCHF immune response. An epitope walk of the five peptides revealed a peptide sequence located in the GN region with high specificity and sensitivity. This peptide sequence, and a sequence downstream, reacted also against sera from survivors of CCHF disease in South Africa. The cross reactivity of these peptides with samples from a geographically distinct region where genetically diverse strains of the virus circulate, enabled the identification of unique peptide epitopes from the CCHF glycoprotein that could have application in development of diagnostic tools. In this study clinical samples from geographically distinct regions were used to identify conserved linear epitopic regions of the glycoprotein of CCHF.